Determinants of Entrepreneurial Education on Entrepreneurial Intention with Entrepreneurial Mindset as a Moderating Variable on Vocational Students - Juwairia, Juwairia; Wardana, Ludi Wishnu; Maharani, Satia Nur (Journal of Applied Business, Taxation and Economics Research, 2024)
With unemployment still high, there have been efforts to develop official and unofficial education to improve the skills of productive human resources. One of the ways used is through Entrepreneurship Education, with the hope that students have the skills to become entrepreneurs and can create jobs for themselves. This research uses a quantitative approach with Partial Least Squares structural equation modeling (PLS-SEM) to predict and confirm the given hypothesis. This research uses Google Forms for data collection on State Vocational School students in Ogan Ilir. Respondents in this study were 360 respondents who were used as research objects. The results showed that Entrepreneurship Education cannot explain Entrepreneurial Intention. However, the Entrepreneurship Education variable can explain the Entrepreneurial Mindset. Furthermore, Entrepreneurship Education will provide more influence on Entrepreneurial Intention, if strengthened by Entrepreneurial Mindset as a mediator variable.